Iron Man is born - Rudnick, Elizabeth; Auman, Brandon (New York : Marvel, 2013)
When the United Nations is attacked, Tony Stark becomes Iron Man to save the day.
Originally published: New York : Marvel, 2011.
At head of title: Earth's mightiest heroes! the Avengers.
Keywords: Robots -- Fiction; Superheroes -- Fiction; Adventure and adventurers -- Fiction; Robots -- Fiction; Superheroes -- Fiction; Radio and television novels; Adventure fiction